İlâhî Fiillerin Nedenliliği Bağlamında Tefsir-Kelâm İlişkisi - (:unkn) unknown (My University, 2016)
Tefsir çalışmaları, tarihî süreci boyunca kelâm tartışmalarından büyük ölçüde etkilenmiştir. Bu etkiyi özellikle müteahhirîn dönemi tefsir metinlerinde bâriz şekilde görmek mümkündür. Bu durum belli ölçüde tabii kabul edilebilir olsa da, Kur'an metninin kendi ortamı, metinsel bütünlüğü ve metin dışı (nüzûl) bağlamı içerisinde anlaşılabilmesi için, başkaca değerlendirmelerden mümkün mertebe bağımsız bir perspektiften ele alınması önem taşımaktadır. Bu makalede kelâmın tefsir kitapları üzerindeki etkisi, ilâhî fiillerin nedenliliği konusuyla ilişkilendirilen Enbiyâ sûresinin 23. âyeti özelinde takip edilmiş ve söz konusu âyetin metin içi ve metin dışı bağlam çerçevesinde ifade ettiği anlamın tespiti yapılmış; ardından bu anlamın ilgili kelâm tartışmalarıyla ilişkilendirilmesinin imkânı tartışılmıştır.

Throughout its long history, the works of tafsir (Qur'anic exegesis) have been substantially influenced by discussions carried out within the discipline of kalam (theology). Particularly, this influence might be observed in post-classical tafsir texts. To a certain extent, this is understandable. However, to understand the Qur'anic text in its own context, in its integrity as a text and in an extra-textual context (nuzul), it seems necessary to consider it through a perspective that is free of other considerations. In this paper we evaluate the influence of kalam on the tafsir works within the context of the commentaries made on Surah Anbiya 21/23 in particular; this verse is associated with the cause of the divine acts. We also designate alternative meanings given to this particular verse within the textual and extra-textual contexts, and finally discuss the possibility of associating these interpretations with contemporary discussions of kalam.
The Relationship Between Tafs?r (Quranic Exegesis) and Kal?m (Theology) in the Context of the Causality of Divine Acts
Keywords: Kültürel Çalışmalar